Prosedur anggaran biaya operasional sebagai alat pengendalian laba pada PT. Bank SULUT GO KCP Ranotana - Tuyu, Anjeli Raysa; Sabijono, Harijanto; Tangkuman, Steven J. (Yayasan Widyantara Nawasena Raharja, 2025)
The banking sector is vital to a country's economic growth. Effective profit control is essential for improving profitability and ensuring business sustainability. The study will examine the procedures for preparing operating cost budgets as a tool for profit control at PT Bank SulutGo KCP Ranotana. We used a descriptive qualitative method, focusing on the budgeting process in relation to profit control mechanisms. The results indicate that: Budgets are prepared several months before the fiscal year begins to ensure readiness. Superiors prepare and communicate the budget for each period to employees. There is a negotiation process in budget preparation. Budget supervision ensures financial management aligns with established plans and objectives. The budgeting approach is mixed, initiated by superiors and finalized by subordinates. Decision-making remains with the superiors, while employees provide input. The budgeting process follows a top-down budgeting model. The findings show that PT Bank SulutGo uses its operational budgeting as a centralised profit control tool.